Intervensi Sistem Produksi Arang Briket Pada Unit Usaha Arang di Dusun Blang Bintang, Desa Blang Thuy, Kabupaten Aceh Besar Melalui Penggunaan Pencetak Arang Briket Sistem Ulir Kontinyu - Machdar, Izarul; Rinaldi, Wahyu; Thalib, Sulaiman (Universitas Syiah Kuala, 2024)
The implementation of technological intervention in a coconut shell charcoal enterprise, facilitated by the integration of a screw briquette machine, has been a transformative initiative undertaken by the Naturi group in Blang Bintang, Blang Thuy Village, Aceh Jaya Sub-district, Aceh Besar District. The comprehensive approach to this intervention included a thorough site survey, extensive socialization efforts, meticulous procurement of equipment and materials, and dedicated training activities. The socialization phase, spanning a duration of two months, was instrumental in ensuring that the aims, objectives, and targets of the planned activities were not only understood but also internalized by the participants. The success of this phase lay in its ability to align with predefined scenarios, fostering a smooth and effective execution of subsequent activities. Results obtained from the intervention showcase the participants' successful acceptance and proficient execution of the introduced technologies. Given the potential risks associated with the handling of the delivered equipment, prioritizing work safety emerged as a critical aspect of the initiative. Looking forward, the focus of the initiative extends beyond its initial phase. Future considerations include strategies to enhance production capacity and the provision of adequate drying areas to meet growing demands. To ensure the longevity of the project, a collaborative effort between the implementer and participants has resulted in the establishment of a dedicated discussion forum through digital media. This platform serves as a dynamic space for ongoing dialogue, knowledge exchange, and the continuous improvement of the technological intervention.